Role of children in the transmission of the COVID-19 pandemic: a rapid scoping review - Luis Rajmil (BMJ Publishing Group, 2020)
Background As a response to the COVID-19 pandemic, most countries have adopted measures of social distance, with the childhood population being one of the main focus of attention in these measures.Methods A rapid scoping review was carried out by searching PubMed to know if children are more contagious than adults, and the proportion of asymptomatic cases in children. Google Scholar and MedRxiv/bioRxiv were also searched. The time period was restricted from 1 December 2019 until 28 May 2020. Only studies published in English, Italian, French or Spanish were included.Results Fourteen out of 1099 identified articles were finally included. Studies included cases from China (n=9 to 2143), China and Taiwan (n=536), Korea (n=1), Vietnam (n=1), Australia (n=9), Geneva (n=40), the Netherlands (n=116), Ireland (n=3) and Spain (population-based study of IgG, n=8243). Although no complete data were available, between 15% and 55%-60% were asymptomatic, and 75%-100% of cases were from family transmission. Studies analysing school transmission showed children as not a driver of transmission. Prevalence of COVID-19 IgG antibody in children <15 years was lower than the general population in the Spanish study.Conclusions Children are not transmitters to a greater extent than adults. There is a need to improve the validity of epidemiological surveillance to solve current uncertainties, and to take into account social determinants and child health inequalities during and after the current pandemic.